The preacher and his preaching : or "Thyself, and the doctrine" (I Tim. 4:16) : helpful information to Christians who are interested in the preparation and presentation of the gospel and teaching message - Gibbs, Alfred Perks, 1890-1967; Horton, A.E. (Kansas City, KA ; Walterick)
Includes reprint of booklet by A.E. Horton : The teaching, interpretation amd application of Scripture
Brethren writer. Date of foreword (1st ed?), 1939. Date of preface to 5th ed. 1964.
Keywords: Preaching